Was Jesus a Political Revolutionary? - Destro, Adriana (Annali di storia dell'esegesi, 2019)
The kingdom that Jesus announced had a clear political-religious content for the Jews of the time and the Romans were well aware of it. But Jesus did not implement political instruments in the strict sense. He situates himself and his action before the advent of the kingdom of God, before the beginning of the kingdom. Jesus considered himself destined to announce the necessity of conversion and forgiveness. A great revolution of society would have come only in the future. Jesus did not consider himself engaged in a political revolution. Jesus’s action, however, caused upheavals in the basic structures of society and his anti-institutional attitude provoked reactions in the elites of villages and cities. It is also probable that the Romans arrested and crucified Jesus in a hurry not because he was a political revolutionary, but because he could represent a danger to the public peace and a threat to imperial power. His success and some aspects of his activity could seem to be signs of insurrection against the Roman dominating power.